Living Alone Is Not Associated With Cardiovascular Events and Hypoglycemia in Patients With Type 2 Diabetes Mellitus - Zhu, Zhaowei; Peng, Zhenyu; Xing, Zhenhua (Frontiers in Public Health, 2022)
Objective: Living alone is often associated with reduced social support. However, there are limited data on the relationship between living alone and cardiovascular events or hypoglycemia in patients with type 2 diabetes mellitus. This study reports a post-hoc analysis of the “Action to Control Cardiovascular Risk in Diabetes (ACCORD)” study. Research Design and Methods: Cox proportional hazard models were used to compare hazard ratios (HRs) for the adverse health events selected as primary endpoints in the study participants; these were compared between those living alone and those living with others. The primary outcomes were hypoglycemia requiring any assistance (HAA), hypoglycemia requiring medical assistance (HMA), and major cardiovascular events (MACEs, including cardiac death, non-fatal myocardial infarction, and non-fatal stroke). Our study included 10,249 participants (2,078 living alone) with a follow-up period of 4.91±1.22 years. Results: After multivariable adjustment, the risk of HAA, HMA, and MACEs did not differ significantly between participants living alone and those living with others (HAA, HR: 0.88, 95% CI: 0.75–1.04, P=0.13; HMA, HR: 1.11, 95% CI: 0.92–1.34, P=0.26; MACEs, HR: 0.98, 95% CI: 0.80–1.19, P=0.82). Participants living alone had higher levels of glycated hemoglobin in the middle follow-up period than those living with others. Conclusions: In patients with T2DM, living alone did not increase the risk of cardiovascular events (cardiac death, non-fatal MI, or non-fatal stroke) and hypoglycemia. Patients living alone had higher Hb1AC levels than those living with others. Clinicians should consider effective blood glucose control regardless of their living arrangement.